Collaborative Learning through Digital Writing: Peer Editing and Feedback in EFL Contexts - Ismail Ismail (Majesty Journal, 2025)
This study investigated the impact of integrating digital writing tools into pre-service EFL teacher training at Universitas Muhammadiyah Enrekang. The research aimed to understand the effectiveness of this approach in enhancing writing skills, fostering creativity, and promoting engagement. A mixed-methods approach was employed, collecting data through digital essay assessments, reflective journals, a focus group interview, and thematic analysis. The findings revealed strong overall performance in digital essay writing, particularly in content and multimodal features. Qualitative data highlighted increased engagement and motivation, significant skill development, and the crucial role of peer collaboration. Challenges included initial technical difficulties and time management. Six key themes emerged: engagement and motivation, challenges and solutions, skill development, peer collaboration, practicality of digital tools, and creativity and expression. The study demonstrates the potential of digital writing to enhance EFL teacher training, fostering creativity and improving writing skills. However, successful implementation requires adequate training, resource allocation, and careful curriculum design. While this study highlights the benefits of digital writing for pre-service EFL teacher training, it has certain limitations. First, the small sample size limits the generalizability of findings to a broader population. Second, technical challenges, such as internet access and familiarity with digital tools, may have influenced participants' engagement. Lastly, the study was conducted over a limited timeframe, preventing an assessment of the long-term impact of digital writing on writing proficiency. Future research should examine these aspects by conducting longitudinal studies, exploring diverse digital writing platforms, and assessing scalability across different educational settings. This study contributes valuable insights into the effective integration of digital writing into EFL teacher education.